2018
DOI: 10.2147/ott.s164276
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of change in microRNA expression profiles of lung cancer A549 cells treated with Radix tetrastigma hemsleyani flavonoids

Abstract: BackgroundThe aim of this study was to determine the inhibition effects of Radix tetrastigma hemsleyani (RTH) flavonoids on human lung adenocarcinoma A549 cells and the underlying molecular mechanism. RTH is an important Chinese traditional herb that has been widely used in cancer therapy. As an important type of active substance, RTH flavones (RTHF) have been shown to have good antiproliferative effects on various cancer cells. MicroRNAs (miRNAs) are small, noncoding RNA molecules that play important roles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…There was a significant decrease in cell proliferation in the miR-4792 mimics and RTHF + miRNA NC groups compared to the control group (miRNA NC group), indicating that RTHF inhibited A549 cell proliferation by upregulating the expression of miR-4792, and the inhibition effect was similar to that of miR-4792 mimics. Compared to the RTHF + miRNA NC group in which only RTHF played a role in cell proliferation inhibition, cell proliferation in the RTHF + miR-4792 inhibitor group was significantly increased, suggesting that miR-4792 played a more important role than other DE-miRNAs found in our previous studies in the cell proliferation inhibition by RTHF 13. The cell viability assays revealed that miR-4792 had effects on inhibiting cell proliferation, and suggested it might have played an important regulatory role in RTHF-mediated inhibition of A549 cell proliferation.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…There was a significant decrease in cell proliferation in the miR-4792 mimics and RTHF + miRNA NC groups compared to the control group (miRNA NC group), indicating that RTHF inhibited A549 cell proliferation by upregulating the expression of miR-4792, and the inhibition effect was similar to that of miR-4792 mimics. Compared to the RTHF + miRNA NC group in which only RTHF played a role in cell proliferation inhibition, cell proliferation in the RTHF + miR-4792 inhibitor group was significantly increased, suggesting that miR-4792 played a more important role than other DE-miRNAs found in our previous studies in the cell proliferation inhibition by RTHF 13. The cell viability assays revealed that miR-4792 had effects on inhibiting cell proliferation, and suggested it might have played an important regulatory role in RTHF-mediated inhibition of A549 cell proliferation.…”
Section: Resultsmentioning
confidence: 51%
“…The purified extract was freeze-dried to RTHF power and then dissolved in Roswell Park Memorial Institute 1640 culture medium to 10 mg/mL and finally filtered through a 0.45 µm filter for use. In our previous experiments, through chemical composition analysis by HPLC–mass spectrometry (MS) and HPLC–MS/MS, we found that RTHF used in this study mainly included six foregone active substances, including kaempferol (PubChem CID: 5280823, 12.57%), kaempferol-3- O -neohesperidoside (PubChem CID: 44575467, 19.11%), malvidin-3-glucoside (PubChem CID: 443652, 10.23%), myricitrin (PubChem CID: 5281673, 8.56%), baohuoside (PubChem CID: 5488822, 9.98%), and isoschaftoside (PubChem CID: 3084995, 13.28%) 13…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the study has found that the content of total flavonoids in leaves of TDG ranges from 13.38 to 28.67 mg· g -1 ( Fan et al., 2017 ). More than 30 flavonoids isolated and identified from TDG, including kaempferol-7-O-α-L-rhamnopyranosyl-3-O-β-D-glucopyranoside (1), apigenin-6-C-α-L-arabinopyranosyl-(1-4)-α-L-rhamnopyranoside (2), and apigenin-8-C-α-L-arabinopyranosyl-(1-4)-α-L-rhamnopyranoside (3), apigenin-6, 8-di-C-β-D-glucopyranoside (4), kaempferol (5), quercetin (6), kaempferol 3-neohesperidoside (7), rhamnocitrin (8), kaempferol-7-O-α-L-rhamnopyranoside (9), aromadendrin (10), kaempferol-3-O-β-D-glucopyranoside (11), isoquercetin (12), nicotifiorin (kaempferol-3-o-rutoside, 13), robinin (14), rutin (15), astragaloside (16), catechin (17), L-epicatechin (18), epigallocatechin (19), procyanidin B2 (20), procyanidin B1 (21), apigenin (22), quercitrin (23), kaempferitrin (24), apigenin-6-C-β-D-glucopyranoside (Isovitexin, 25), apigenin-8-C-α-L-rhamnopyranosyl-(1-2)-β-D-glucopyranoside (Vitexin-2-O-rhamnoside, 26), apigenin-8-C-β-D-glucopyranoside (Vitexin, 27), apigenin-8-C-β-D-glucopyranoside-(1-4)-β-D-glucopyranoside (Vitexin-4’’-O-glucoside, 28), orientin (29), isoorientin (30), malvidin-3-glucoside (31), myricitrin (32), baohuosid I (33), and isoschaftoside (34) ( Liu, 2000 ; Liu et al., 2002 ; Li et al., 2003 ; Guo, 2013 ; Zeng, 2013 ; Fan et al., 2014 ; Fu et al., 2015 ; Lin et al., 2015 ; Liu et al., 2018 ). The structure of some flavonoids is shown in Figure 2 , with the names of all constituents being listed in Table 1 .…”
Section: Phytochemistrymentioning
confidence: 99%